Studies on hepatoprotective effects of Vietnamese medicinal plants - Pham, Ngoc Khanh; Bauerova, Katarina; Manh Cuong, Nguyen (Vietnam Journal of Science and Technology, 2023)
The liver is a major organ of the human and animal body, playing an important role in metabolism, detoxification and immunomodulation. When liver tissue is damaged, liver function will decrease, leading to liver diseases such as liver fibrosis, cirrhosis, and liver cancer. Medicinal plants and natural products have provided a source of new drug candidates for the prevention and treatment of liver diseases. This review is based on scientific publications on Vietnamese plants investigated for their hepatoprotective activity during the period from 1998 to 2022. 51 medicinal plants, 38 phytoconstituents, and 8 hepatoprotective herbal formulations of Vietnamese-origin have been reported to protect the liver from the harmful effects induced by hepatotoxins, typically CCl4 or paracetamol. Each plant’s information, including its botanical name, family, part of the plant used, local name, chemical constituents, extracts or fractions used, dosage, model used, parameters obtained, histopathology, and results of hepatoprotective studies, is displayed. Also discussed is the possible mechanism of action of these hepatoprotective plants.